The stop and search of minors: A 'vital police tool'?. (July 2018) - Flacks, Simon
Police stop and search powers have been widely criticized for the disproportionate manner in which members of black and ethnic minority communities are targeted. However, the use of such powers on minors in England and Wales has largely escaped comment, despite good evidence that such practices are harmful and counter-productive. Whilst data on the stop and search of under-10s and even toddlers has been reasonably widely reported by the mass media, there has been little interest in the welfare of older children who are subject to such police powers. Drawing on police data, qualitative research and information obtained through Freedom of Information requests, this article considers the relationship between potentially corrosive stop and search practices, young people's use of public space and the question of vulnerability. It is concluded that policy and practice around the use of such powers should be amended to take account of the specific needs of individuals under the age of 18, and that children's welfare should be a central consideration.